Use of technology in evidence-based programs for child maltreatment and its impact on parent and child outcomes - Tiwari, Ashwini; Recinos, Manderley; Garner, Jamani; Self-Brown, Shannon; Momin, Rushan; Durbha, Sadhana; Emery, Vanessa; O’Hara, Kathryn; Perry, Elizabeth; Stewart, Regan; Wekerle, Christine (Frontiers in Digital Health, 2023)
Introduction Technology has been used in evidence-based child maltreatment (CM) programs for over a decade. Although advancements have been made, the extent of the application of technology in these programs, and its influence on parental and child outcomes, remains unclear within the context of changes that emerged because of the COVID-19 pandemic. This scoping review provides a contextualized overview and summary of the use of technology in evidence-based parenting and child programs serving families impacted by child maltreatment and the effects of technology-enhanced programs on target outcomes. Materials and methods Using Arksey and O'Malley's methodological framework, we searched seven databases to identify peer-reviewed and grey literature published in English from 2000 to 2023 on evidence-based programs, according to the California Evidence-Based Clearinghouse (CEBC), that included technological supports for two populations: at-risk parents for child maltreatment prevention, and children and youth 0–18 years exposed to child maltreatment. All study designs were included. Results Eight evidence-based parenting programs and one evidence-based child trauma program were identified as using technology across a total of 25 peer-reviewed articles and 2 peer-reviewed abstracts meeting inclusion criteria (n = 19 on parent-level programs; n = 8 on child-level programs). Four studies were published in the context of COVID-19. Two main uses of technology emerged: (1) remote programmatic delivery (i.e., delivering all or part of the program virtually using technology) and (2) programmatic enhancement (i.e., augmenting program content with technology). Improvements across parenting and child mental health and behavioral outcomes were generally observed. Discussion Technology use in evidence-based child maltreatment programs is not new; however, the small sample since the start of the COVID-19 pandemic in this review that met inclusion criteria highlight the dearth of research published on the topic. Findings also suggest the need for the inclusion of implementation outcomes related to adoption and engagement, which could inform equitable dissemination and implementation of these programs. Additional considerations for research and practice are discussed.